Pendugaan Tingkat Produktivitas Lahan untuk Tanamanan Kelapa Sawit (Elaeis guineensis jacq) di Kabupaten Bangka dan Bangka Barat - Apong Sandrawati; Aldi Putra Guntara (Fakultas Pertanian Universitas Padjadjaran, 2016)
The aimed of this research was to find out the level of agricultural land productivity with Storie Index Method and predict oil palm productivities based on land productivity. This research had been done since May until August 2014 at Bangka and West Bangka District. The landuse consisted with forest, crop fields, plantation, paddy soils and heath. The slopes consisted with vary on declivity; 0-8 %, 8-15 %, 25-40 % dan > 40 %, meanwhile the soil’s great group consisted with Haplohemists, Hapludox, Endoaquepts, Hydraquent, Udipsamments dan Dystrudepts. The district was on two type of rain fall, there was 2750 and 3000 mm/year. Analisys unit was land units that build from overlay those land variable. There was 24 land unit as research analisys unit. Data analisys used Storie Index Rating as parametrics approach. The result of this research showed that the level of productivity in Bangka and West Bangka District was excellent, good, moderate, and poor. The most extensive land quality is at grade 3 or medium quality is amounted to 394.668, 97 Ha or 70,49 % of total areas. Based on land productivity levels, productivity of oil palms counted that higher potential was in medium class with productivities range 11-18 tonnes/Ha/years. This area was speard 536.242,34 Ha or 95,78 % of total areas.Key words: Land productivity, storie index, oil palm productivities